Israeli Society in the Twenty-First Century : Immigration, Inequality, and Religious Conflict - Goldscheider, Calvin (Book collections on Project MUSE., 2015)
A data-based analysis of social life and social problems in contemporary Israel that draws a vivid portrait of a dynamic and rapidly changing society.